A reassessment of current volcanic emissions from the Central American arc with specific examples from Nicaragua - Mather, T; Pyle, D; Tsanev, V; McGonigle, A; Oppenheimer, C; Allen, A (2006)
The Central American volcanic arc supplies a significant proportion of the persistent annual global sulphur dioxide emissions from volcanoes. In November/December 2003, we completed a survey of the arc section from Mombacho to San Cristóbal in Nicaragua recording individual mean fluxes of 800, 530 and 220 Mg day-1 in the plumes from San Cristóbal, Telica and Masaya, respectively. An assessment of fluxes published since 1997 along the entire Central America arc yields a mean total arc flux of SO2 of 4360 Mg day-1 or 8-16% of the annual estimated global volcanic SO2 flux to the troposphere. New field data shows that Masaya volcano continues to show stable HCl/SO2 and HF/SO2 ratios, suggesting a sustained flux of these components of ∼220 and 30 Mg day-1, respectively (1997 to 2004). Masaya's plume composition also appears to have been stable, between 2001 and 2003, with respect to all the particulate species measured, with significant fluxes of SO42- (4 Mg day-1), Na+ (0.9-1.3 Mg day-1) and K+ (0.7 Mg day-1). Extrapolating the Masaya plume species ratios to the entire Central American arc gives mean HCl and HF fluxes of 1300 and 170 Mg day-1 and a particulate sulphate flux of 40 Mg day-1 for 1997 to 2004, although without further understanding of the degassing processes and sources at depth of these different volatiles, these arc-scale estimates should be treated with caution. Combining our arc scale mean SO2 flux with published measurements of volcanic gas compositions with respect to CO2 and H2O allows us to estimate mean CO2 fluxes of 4400-9600 Mg day-1 and H2O fluxes of 70,000-78,000 Mg day-1 for the arc. Preliminary comparisons of these estimates of outgassing rates with published volatile input fluxes into the Central American subduction zone, suggest that Cl is more efficiently recycled through the subduction zone than CO2. The results for H2O are inconclusive. © 2005 Elsevier B.V. All rights reserved.